SISTEM INFORMASI PEMBELIAN PENJUALAN DILENGKAPI DECISSION SUPPORT SYSTEM UNTUK PENENTUAN SUPPLIER - Egie Imanda; Doro Edi (Jurnal Teknik Informatika dan Sistem Informasi, 2016)
PT. Electrical MBS address at the Rukan City Garden Maisonete A 1/5 East Cengkareng, West Jakarta is a PT engaged in the sale of electrical equipment that is being developed in the field of buying and selling daily necessities. The author conducted research based on the company's business processes. Managed business process is ordering, purchasing and sales. Research conducted covering all business processes that originally done manually later on Automated via a web-based application system. The author also help the company to see the reports generated by the existing business processes. Moreover, the author also assist the company in determining the supplier for each item that is using the Decision Support System with Analytical Hierarchy Process method. Aplication made is expected to help the company to run its business and simplify the control of the company in general.